Development of ibuprofen-loaded nanostructured lipid carrier-based gels: characterization and investigation of in vitro and in vivo penetration through the skin - Sütő B (Dove Medical Press, 2016)
Blanka Sütö,1 Szilvia Berkó,1 Gábor Kozma,2 Ákos Kukovecz,2,3 Mária Budai-Szucs,1 Gábor Erös,4,5 Lajos Kemény,4 Anita Sztojkov-Ivanov,6 Róbert Gáspár,6 Erzsébet Csányi11Department of Pharmaceutical Technology, Faculty of Pharmacy, 2Department of Applied and Environmental Chemistry, 3MTA-SZTE “Lendület” Porous Nanocomposites Research Group, 4Department of Dermatology and Allergology, 5Department of Oral Biology and Experimental Dental Research, 6Department of Pharmacodynamics and Biopharmacy, University of Szeged, Szeged, HungaryAbstract: An ibuprofen-loaded nanostructured lipid carrier (IBU-NLC) was developed for enhanced skin penetration to improve the treatment of osteoarthritis and other musculoskeletal diseases. The mean particle size was 106 nm, with a spherical morphology, a smooth surface, and a zeta potential of −18.4 mV. X-ray diffraction studies revealed the amorphous state of the lipid matrix. Both Raman spectroscopy and Fourier transformation infrared analysis indicated no major shifts in the spectra of the formulations, which suggest rapid drug dissolution from the nanoparticles. The drug loading was 9.85%, and the entrapment efficiency was 98.51%. In vitro release of the NLC dispersion, in vitro permeation, and in vivo animal studies of IBU-NLC gel all confirmed that the permeation of IBU was significantly better than that of a reference after 6 hours. In conclusion, IBU-NLC gel is of great potential to enhance drug permeation through the skin and hence the efficacy of the treatment of chronic joint inflammation.Keywords: ibuprofen, nanostructured lipid carriers, skin penetration, SKH-1 hairless mice, osteoarthritis